The Early Facilitative and Late Contextual Specific Effect of the Color Red on Attentional Processing - Xia, Tao; Qi, Zhengyang; Shi, Jiaxin; Zhang, Mingming; Luo, Wenbo (Frontiers in Human Neuroscience, 2018)
Many studies have proved that color represents a variety of emotionally meaningful information. Researchers have proposed that context information endows colors with different associated meanings, and elicits corresponding behavior. Others have contended that the color red intensifies the stimulus’ existing valence or motivation tendency in the early processing step. The present study attempts to incorporate these two effects of the color red to explore their differences in a dot probe task, using event-related potential (ERP). Our ERP results indicate that the color red intensifies the initial attention to emotion-congruent conditions, as indicated by the P1 component. However, the colors red and green lead to sustained attention to the expression of anger and happiness, respectively, but not fear, as shown by the late positive complex component (all results are available at: https://osf.io/k3b8c/). This study found the different processing stages of the effect of the color red during attentional processing in a discrete emotional context, using ERPs, and may refine the Color-in-Context theory.